AN ANALYSIS OF CONTRACTION IN VOICE NOTE ALBUM BY CHARLIE PUTH - Nasution, Ajeng Tria Wasesha; Salsabila, Ananda Pasha; Danial, Muhammad; Syakila, Farah; Nurmala, Dewi (PHILOLOGY Journal of English Language and Literature, 2025)
Song language functions as a means of expressing emotions, conveying messages, strengthening themes, creating beauty, building atmosphere, motivating listeners, and strengthening cultural ties and community identity. Song lyrics are written works describing experiences, feelings, and stories with explicit and implied content. To find out the construction, researchers analyzed voice notes by Charlie Puth. This research uses qualitative research and analyses data using Wolcott's theory, which states that language style consists of two aspects: language style based on sentence structure and language style based on meaning. There are thirteen songs in the voice note album; analyze all thirteen. Contraction involves joining two free morphemes, where one becomes bound, forming a single morpheme. The constructions analysed are finite constructions and non-finite constructions. The results are that there are 29 finite contractions, and 22 non-finite contractions found.